FUNGSI DAN MAKNA PERTUNJUKAN WAYANG DI KRECEK - Tri Mulasno (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
Abstract Wayang kulit purwa (shadow puppet) Performance Function and Meanings, in the village of Krecek. Wayang kulit purwa performance with the story Baratayudha at Syawalan Ceremony is a tradition held annually by the community of Dukuh Dadimulyo, in the village of Krecek, Kecamatan Delanggu, Kabupaten Klaten. This wayang kulit purwa performance is believed by the community to be such an important thing in their lives that they do their best to hold the performance once a year. The research on the wayang kulit purwa performance aimed at understanding and finding out the impacts brought about by the performance which is still held annually by the community. In addition to this, this study aimed to find out the function and meanings of the performance as well as the messages told by the puppeteer. Wayang kulit purwa performance with the story Baratayudha at Syawalan ceremony in Dukuh Dadimulyo, in the village Krecek, is for the community a means of request and medium to express their gratitude to sing bahureksa desa (the spirit guarding the village) or to Almighty God. By carrying out the performance, the community hopes that their lives will be protected so that theyÂ can live of life which is happy, prosperous, secure and peaceful, both physicallyÂ and spiritually and can escape from calamities.Key words: Village clean ceremony, peace and prosperityÂ